Enrollment Practices in Early Education Centers: Examining Implementation in the Arkansas State Pre-K Program - Gerilyn Slicker; Jason T. Hustedt; Melissa Stoffers; Cara L. Kelly (AERA Open)
Enrollment in high quality pre-kindergarten (pre-K) programs is associated with positive outcomes for children; yet, inequities in access are prevalent. This mixed methods study is a comprehensive examination of early care and education (ECE) centers’ enrollment practices with a specific focus on enrollment of children from underserved backgrounds in Arkansas Better Chance (ABC) pre-K programs compared with non-ABC programs. Logistic regression models using a statewide sample of ECE centers reveal that ABC programs are typically fully enrolled and enroll underserved populations—including children in impoverished and rural areas and children with disabilities—at higher rates than non-ABC programs. Qualitative interviews reveal enrollment facilitators and barriers in both ABC and non-ABC programs, including aspects of centers, surrounding communities, and state policies. Results suggest that policies such as deliberately setting and implementing certain enrollment priorities may enhance equitable ECE access.